DAMPAK PEMBATALAN KEBERANGKATAN HAJI BAGI CALON JEMAAH HAJI LANJUT USIA DI KEMENTERIAN AGAMA KABUPATEN MAJENE TAHUN 2022 (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2023)
The main problem in this research is the impact of the cancellation of Hajj departure for prospective elderly pilgrims at the Ministry of Religion of Majene Regency in 2022. The formulation of the problem in this research is: What is the impact of canceling Hajj departure for prospective elderly pilgrims at the Ministry of Religion of Majene Regency? And what are the motivational efforts made by the Ministry of Religion of Majene Regency for prospective elderly pilgrims who cancel their pilgrimage in 2022? This type of research is qualitative, with a missionary and communication approach. The sources of this research are prospective elderly pilgrims, the Head of the PHU Section, and the Administration Staff of PHU Data Presentation and Publication. Data collection methods used in this study were observation, interviews, and documentation. The results of this study explain that there are two forms of impact from canceling the pilgrimage departure for prospective elderly pilgrims at the Ministry of Religion of Majene Regency, namely the positive impact and the negative impact. The negative impact is the negative result of canceling the departure of the haj for prospective elderly pilgrims, namely worry about age, worry about rising haj fees, and changes in behavior. Meanwhile, the positive impact is a positive result of canceling the departure of the hajj for the elderly hajj pilgrims, namely surrendering to Allah swt., maintaining health, and preparing for a more mature pilgrimage. Motivating efforts carried out by the Ministry of Religion of Majene Regency, namely through face-to-face and outreach.